Studies on Strategic Planning for the Future Development of the Tribes A Case Study of Four Tribal Agencies in the Southern States of India - Planning Commission (Planning Commission, 1996)
The tribals are, by and large, children of nature, their life style being conditioned by their eco-system. At present there are approximately 200 million tribal people1, roughly 4 percent of the global population. They are found in all regions of the world and number among the poorest of the poor India is the largest concentration of tribal people anywhere in the world except perhaps in Africa. According to 1991 census, the population of the scheduled tribes in the country was 67.76 millions, constituting about 8.08 per cent of the total population, approximately one tribesman for every thirteen Indians. Areas inhabited by tribals constitute a significant past of the backward areas of the country. On the whole it is estimated that the predominant tribal areas comprise of about 15 percent of the total geographical area of the country.
Planning Commission Government of India
Planning Commission Government of India